Carbon nanotube/polymer nanocomposites: A study on mechanical integrity through nanoindentation. Issue 8 (19th April 2014) - Koumoulos, Elias P.; Jagdale, Pravin; Kartsonakis, Ioannis A.; Giorcelli, Mauro; Tagliaferro, Alberto; Charitidis, Constantinos A.
<x xml:space="preserve">Abstract</x> Carbon nanotubes (CNTs) are under intense investigation in materials science owing to their potential for modifying the mechanical proprieties of their composites. In this work, nanomechanical and nanotribological properties of polymer composites, reinforced with multiwall carbon nanotubes (MWCNTs) and single wall carbon nanotubes (SWCNTs), have been studied using the nanoindentation and nanoscratch technique. In particular, three different epoxy resins reinforced using several percentage of two different types of MWCNTs have been studied (range 0–7 wt%). Another resin was reinforced using MWCNTs (range 0–2.5 wt%) and SWCNTs (range 0–5 wt%) as fillers. Hardness and elastic modulus using nanoindenter instrument have been evaluated, while the coefficient of friction of the nanocomposites is obtained using nanoscratch. The results show an evident dependence with the percentage of CNTs. For all types of resins, an optimum in nanomechanical properties is found at intermediate levels of CNTs filling. POLYM. COMPOS., 36:1432–1446, 2015. © 2014 Society of Plastics Engineers